PENINGKATAN DISPOSISI MATEMATIKA MAHASISWA STKIP PESISIR SELATAN PADA MATA KULIAH STATISTIKA DASAR DENGAN PENERAPAN PROBLEM BASED LEARNING - Syafti, Okviani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2019)
Mathematical disposition is an attitude that students need as students to survive in facing problems, take responsibility in their learning, and develop good work habits in mathematics. However, the mathematical disposition of STKIP Pesisir Selatan students while attending basic statistics lectures is still far from expectations. For this reason, a learning model is needed to overcome them. One model that can be used is problem based learning. The purpose of this study is to find out how to increase the mathematical disposition of STKIP Pesisir Selatan students in basic statistics courses before and after learning problem based learning and whether the improvement is significant. All populations were sampled, namely students of mathematics and ICT education courses taking basic statistics courses in the even semester 2018/2019. This type of research is Quasi Exspriment with One Group Pretest-Posttest Design research design. The research data were obtained from a questionnaire given before and after the experiments were carried out. Data analysis used N-gain test to measure the increase in mathematical disposition and continued by paired sample t test to see the significance of the increase. The results of the analysis show that the increase in mathematical disposition of STKIP Pesisir Selatan students with the application of problem based learning in basic statistical subjects has increased quite well, but the increase that occurred was not significant.